Classification of Mathematical Poetry - Radoslav Rochallyi (Hyperrhiz, 2023)
In this statement I aim to create at least a partial classification of mathematical poetry as part of a large group of experimental poetry. I have created a primary classification according to pure mathematics, knowing that it is incomplete and can be extended within and towards other mathematical disciplines, such as applied mathematics or borderline disciplines. All unfamiliar artistic forms in the text are poems themselves. However, it can be used for an analysis of any poem.